Devising Trainings to Enhance the Capabilities of Children With Autism Spectrum Disorder to Cope With Metaphor: A Review of the Literature - Melogno, Sergio; Pinto, Maria Antonietta (Frontiers in Communication, 2022)
This article reviews the literature reporting on the trainings implemented with children with Autism Spectrum Disorder (ASD) without intellectual disability to enhance their capability to cope with metaphor comprehension. The studies in this review can be classified into two main strands of thought, behavioral-analytic and cognitive-psycholinguistic, respectively. Beyond some basic similarities all these studies share in their attempt at training children to consider the semantic features of metaphors, the mental pathways activated by those trainings are based on different cognitive and linguistic processes. The trainings based on the behavioral-analytic perspective teach the meaning of metaphors by making an extensive use of prompts: iconic, echoic, and textual. In the trainings based on the cognitive-psycholinguistic perspective, instead, a wide range of activities are devised to stimulate children’s analytical abilities to cope with semantic relations in metaphors. A significant part of these activities are jointly conducted between adult and children, and aimed at promoting the child’s autonomy. Among the most interesting theoretical challenges stemming from the abovementioned studies, this review considers the spontaneous creation of original metaphors in children with ASD when solicited to understand metaphorical expressions. This unexpected reaction highlights the complexity of the relationships between metaphor comprehension and production in children with ASD.